Preparation and Characterization of Hybrid Chitosan/PEO–Silica Membrane Doped with Phosphotungstic Acid for PEM Fuel Cell Application. Issue 1 (2nd January 2019) - Jesuraj, Kalaiselvimary; Manimuthu, Ramesh Prabhu
ABSTRACT: In an effort to improve the proton conductivity of the s-Chitosan/PEO/s-SiO2 membranes, a heteropoly acid such as phosphortungstic acid/Sulfosuccinic acid as a cross-linker is incorporated in the polymer matrix. The membranes show that s-SiO2 nano particles are dispersed within the membranes uniformly and indicating the good organic compatibility of s-SiO2 particle with PWA/SSA. The conductivity is found to increase in the order of10 −1 Scm −1 at 303K for increasing the PWA acid dopant. The physicochemical properties of the films are successively characterized by water uptake, IEC and mechanical stability. The results suggest that s-CS/PEO/s-SiO2 /PWA composite membranes suitable for fuel cell. GRAPHICAL ABSTRACT: GRAPHICAL ABSTRACT